Terotechnology XII 12th International Conference on Terotechnology, 20-21 October 2021, Kielce, Poland - Radek, Norbert (Materials research proceedings ;, 2022)
"Terotechnology is concerned with the installation, commissioning, maintenance, replacement, and removal of plant machinery and equipment. It also includes operation and design aspects, and related subjects and practices. Keywords: Flow Control Valve, Boiling Heat Transfer, Laser Treated Heaters, Laser Micro Machining, Surface Laser Micropatterning, Adhesive Joints, WC-Co Coatings, Diamond-Like Carbon Coatings, TiO2 Coatings, Weathering of Paint Systems. Rolling Stock, Cellular Automata, High Strength Concrete, Concrete Composites, Thermal Sensations, Intelligent Buildings, Sulphuric Acid, Corrosion Resistance of Coatings on Steel, Evaluating the Technological Modernity of Machines, Computer Simulation Techniques, Production Management, TNT Storage, Powder Metallurgy, Graphene Oxide, Rail Head Operational Crack, Aluminum Castings, Non-Destructive Testing, Automotive Industry Case Studies, Quality Assessment, Bearing Shell Casting, Rail Vehicles, Fuels in Rail Transport, Fire Hazard, Mobility Assessment for Tracked Vehicles, Laser Welding, Helical Metal Expansion Joints, Steel Joints, Flash Butt Welded Rail Joints, Gas Face Seals, Design Parameters of Ball Bearing, Neural Network Structure, Prescriptive Maintenance Strategy, Unmanned Aerial Vehicles, Urban Traffic Noise, Textile Cleaning Processes."--